1984
DOI: 10.1002/bms.1200111103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metabolic fuel on the13C/12C ratio of breath CO2

Abstract: Natural differences in 13C/12C ratios of various metabolic fuels can produce systematic changes in the 13C/12C ratio of breath CO2, and therefore introduce errors into 13CO2 breath tests. To gain insight into the potential problem, we compared 13C/12C ratios of plasma macronutrients to those of breath CO2 under conditions that should alter the percentages of carbohydrate and lipid being oxidized. In rats, 48 h of starvation decreased the 13C/12C ratio of breath CO2 by 3.5%. At this time the 13C/12C ratio of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 13 publications
(2 reference statements)
2
50
0
Order By: Relevance
“…Physical activity was kept at minimum in order to obtain an accurate estimation of CO 2 production rate (VCO 2 ). Furthermore, carbohydrate and lipid stores have been shown to have different 13 C abundance, with fat more depleted than carbohydrate (Schoeller et al, 1984). Therefore, minimal activity conserves glycogen stores and limits fat oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was kept at minimum in order to obtain an accurate estimation of CO 2 production rate (VCO 2 ). Furthermore, carbohydrate and lipid stores have been shown to have different 13 C abundance, with fat more depleted than carbohydrate (Schoeller et al, 1984). Therefore, minimal activity conserves glycogen stores and limits fat oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies confirmed that banded bats cover up to approximately 2000 km (one way) along their annual migration [7,29], which is one of the longest recorded migratory movements for a bat worldwide [3]. To determine whether P. nathusii oxidize 13 C-enriched proteins from insects that they hunt en route, or whether they oxidize 13 C-depleted endogenous fatty acids from adipocyte TAG, we determined the source of oxidized substrates in migratory P. nathusii by measuring the stable carbon isotope ratios (d 13 C V-PDB ) of exhaled breath; breath d 13 C V-PDB matches closely d 13 C V-PDB of the pool of oxidized substrates [30,31]. We hypothesized that migratory P. nathusii oxidize insect proteins or a mixture of exogenous insect proteins and endogenous fatty acids, because sedentary insectivorous bats are known to oxidize dietary nutrients or endogenous fatty acids from adipocytes according to whether or not they have fed recently [24].…”
Section: Introductionmentioning
confidence: 99%
“…We fed 10 bats each with 5 mg 13 C-labelled glycine (C1-glycine; Euriso-Top GmbH, SaarbrĆ¼ cken, Germany) and seven bats each with 5 mg 13 C-labelled palmitic acid (C1-palmitic acid; EurisoTop GmbH) to assess whether migratory bats oxidize either of the substrates, and, if so, how much of the orally fed dosage would be used for oxidation over the experimental period. Breath collection followed the procedure described for experiment II with the difference that breath samples were collected at times 0, 5,10,15,20,25,30,35,40,45, 50, 55, 60, 75 and 90 min. Stable isotope ratios of breath were analysed as described earlier.…”
mentioning
confidence: 99%
“…The effects on basal I3C abundance of the ingestion of constituents other than the corn starch at breakfast (10) and during the day (13), as well as those of the activity (13,14), were assessed on a separate day in the healthy children and in the children with cystic fibrosis when taking enzyme supplements and also when not taking them. The experimental design was similar to the study days, with the breakfast consisting of starch, milk, and beet sugar as did the test breakfasts, the only difference being that the starch was from rice, which has a low 13C abundance (10,13,14).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental design was similar to the study days, with the breakfast consisting of starch, milk, and beet sugar as did the test breakfasts, the only difference being that the starch was from rice, which has a low 13C abundance (10,13,14). The I3C content of this blank breakfast was -26.3 d per mil.…”
Section: Methodsmentioning
confidence: 99%